2013
DOI: 10.1055/s-0033-1337695
|View full text |Cite
|
Sign up to set email alerts
|

Biotin-responsive basal ganglia disease: a treatable differential diagnosis of Leigh syndrome

Abstract: Biotin-responsive basal ganglia disease (BBGD) is an autosomal recessive disorder, which is caused by mutations in the SLC19A3 gene. BBGD typically causes (sub)acute episodes with encephalopathy and subsequent neurological deterioration. If untreated, the clinical course may be fatal. Our report on a 6-year-old child with BBGD highlights that the disease is a crucial differential diagnosis of Leigh syndrome. Therefore, biotin and thiamine treatment is recommended for any patient with symmetrical basal ganglia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Biotin‐ or thiamine‐responsive encephalopathy type or thiamine metabolism dysfunction syndrome 2 (THMD2), formerly known as biotin responsive basal ganglia disease is an autosomal recessively inherited disease caused by mutations in thiamine transporter type 2 (ThTR‐2), encoded by SLC19A3 (#606152) . Phenotypes linked to SLC19A3 deficiency include Leigh encephalopathy and Wernicke encephalopathy . Yamada et al reported four Japanese patients who presented with epileptic spasms in early infancy, severe psychomotor retardation, brain atrophy, and bilateral thalamic and basal ganglia lesions.…”
Section: Inborn Errors Of Metabolism Leading To Thiamine Dysfunction mentioning
confidence: 99%
“…Biotin‐ or thiamine‐responsive encephalopathy type or thiamine metabolism dysfunction syndrome 2 (THMD2), formerly known as biotin responsive basal ganglia disease is an autosomal recessively inherited disease caused by mutations in thiamine transporter type 2 (ThTR‐2), encoded by SLC19A3 (#606152) . Phenotypes linked to SLC19A3 deficiency include Leigh encephalopathy and Wernicke encephalopathy . Yamada et al reported four Japanese patients who presented with epileptic spasms in early infancy, severe psychomotor retardation, brain atrophy, and bilateral thalamic and basal ganglia lesions.…”
Section: Inborn Errors Of Metabolism Leading To Thiamine Dysfunction mentioning
confidence: 99%
“…Cogwheel rigidity is a classic feature, and parkinsonism may develop in untreated individuals . Brain imaging is often diagnostic and shows a “Leigh syndrome–like” pattern with central bilateral necrosis in the head of the caudate and putamen . Vasogenic edema is observed during the acute presentation whereas atrophy and gliosis in the affected regions are observed in chronic disease .…”
Section: The “Top Ten” Of Treatable Iems Presenting With Movement Dismentioning
confidence: 99%